Performing the piano works of Maria Szymanowska: considerations of authenticity, history, and gender - Wang, Chenxi (2025)
Over the past three decades, Historically Informed Performance (HIP) has become increasingly mainstream. Once confined to eighteenth-century music, it now informs approaches to nineteenth-century music and beyond, presents challenges to performers. For modern pianists, such historical considerations mean that they need to be aware of issues relating to authenticity when playing nineteenth-century repertoire. Yet what kind of authenticity should one seek? In addition, scholarly attention has focussed on only a small number of male canonical figures. But the piano in the nineteenth century was mainly played by females. Does gender make a difference? How, for instance, should a modern pianist perform works by an early nineteenth-century female pianist? Should one scour manuscripts for clues left by the composer? Should one play on a period instrument? Does one need to apply earlier techniques? Or is one supposed to lead the performance with one’s own instincts and feelings? How should historical evidence inform performance? And how might a pianist demonstrate their own take on the issues through a recital?